Infertility and ovarian follicle reserve depletion are associated with dysregulation of the FSH and LH receptor density in human antral follicles - Regan, Sheena; Knight, P.; Yovich, John; Stanger, J.; Leung, Y.; Arfuso, Frank; Dharmarajan, Arunasalam; Almahbobi, Ghanim (Elsevier Ireland Ltd, 2017)
The low take-home baby rate in older women in Australia (5.8%) undergoing IVF is linked to the depletion of the ovarian reserve of primordial follicles. Oocyte depletion causes an irreversible change to ovarian function. We found that the young patient FSH receptor and LH receptor expression profile on the granulosa cells collected from different size follicles were similar to the expression profile reported in natural cycles in women and sheep. This was reversed in the older patients with poor ovarian reserve. The strong correlation of BMPR1B and FSH receptor density in the young was not present in the older women; whereas, the LH receptor and BMPR1B correlation was weak in the young but was strongly correlated in the older women. The reduced fertilisation and pregnancy rate was associated with a lower LH receptor density and a lack of essential down-regulation of the FSH and LH receptor. The mechanism regulating FSH and LH receptor expression appears to function independently, in vivo, from the dose of FSH gonadotrophin, rather than in response to it. Restoring an optimum receptor density may improve oocyte quality and the pregnancy rate in older women.